2013
DOI: 10.1136/bmjopen-2013-003105
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive screening improves the predictive value of stroke severity scores for functional outcome 3–6 months after mild stroke and transient ischaemic attack: an observational study

Abstract: ObjectivesTo investigate the prognostic value of the neurocognitive status measured by screening instruments, the Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE), individually and in combination with the stroke severity scale, the National Institute of Health Stroke Scale (NIHSS), obtained at the subacute stroke phase or the baseline (≤2 weeks), for functional outcome 3–6 months later.DesignProspective observational study.SettingTertiary stroke neurology service.Participants400 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 16 publications
(18 reference statements)
1
41
1
Order By: Relevance
“…Furthermore, in a previous study, we reported that brief cognitive tests (MMSE and MoCA) administered during the acute stroke phase might predict functional outcome and cognitive impairment determined by a formal neuropsychological evaluation at 3-6 months after stroke. 21,45 Fifth, we did not evaluate potential confounders for cognitive decline such as treatment with antihypertensive, statins, and antithrombotic drugs and duration of the vascular risk factors. Sixth, only 59 out of 100 baseline subjects completed both TCD investigation and cognitive tests.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a previous study, we reported that brief cognitive tests (MMSE and MoCA) administered during the acute stroke phase might predict functional outcome and cognitive impairment determined by a formal neuropsychological evaluation at 3-6 months after stroke. 21,45 Fifth, we did not evaluate potential confounders for cognitive decline such as treatment with antihypertensive, statins, and antithrombotic drugs and duration of the vascular risk factors. Sixth, only 59 out of 100 baseline subjects completed both TCD investigation and cognitive tests.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, MoCA baseline score was an independent determinant of PSCI with an odds ratio 1.4 for each test point lost. 20 MoCA score was also associated with poor functional status measured with the modified Rankin Scale at 3 to 6 months in patients with ischemic stroke or transient ischemic attack 14 and at 12 months in patients with subarachnoid hemorrhage.…”
Section: Strokementioning
confidence: 95%
“…10,11,14,[16][17][18][19] These exclusion criteria led to apply MoCA mostly in mild-to-moderate patients with stroke, usually with first-ever ischemic stroke, without other major disorders or severe aphasia. The fact that patients with severe neurological status or aphasia cannot be tested with MoCA is not necessarily a major limitation of this tool because these patients are already candidates for specific rehabilitation programs or long-term care strategies.…”
Section: Strokementioning
confidence: 99%
See 2 more Smart Citations